MERDEKA CURRICULUM AT SDIT IRSYADUL ‘IBAD FROM THE PERSPECTIVE OF RECONSTRUCTIONISM PHILOSOPHY - Fauzi Fadliansyah; Arita Marini; Linda Zakiah; Fauzi Fadliansyah (PIONIR: JURNAL PENDIDIKAN, 2025)
The Independent Curriculum is a development of the K13 curriculum that focuses on developing students' talents, potentials, and interests by digitizing learning with technology. This curriculum begins the Society 5.0 era, where technology dominates. The Independent Curriculum consists of four schools of educational philosophy, each of which has a different way of building a curriculum. One of them is the Reconstructionist philosophy. To find out what dominates the philosophy of education, the development of the independent curriculum must be reviewed from a Reconstructionist perspective. This will make it possible to determine the basis of the curriculum and its results. A qualitative method was used in this study. The primary source of this study came from scientific literature, while secondary sources came from supporting sources such as essays, papers, and interview results with teachers. The results of the study show that reconstructionism is an important component in changing the SDIT Irsyadul Ibad curriculum to the Independent Curriculum. Keyword: Independent Curriculum, Philosophy Of Education, Reconstructionism.